THE COMPARISON ANALYSIS OF INDONESIAN COMPANY'S FINANCIAL PERFORMANCE BEFORE AND DURING THE COVID-19 PANDEMIC - Lailah Fujianti; Mira Munira; Sri Lestari Tindaon (INQUISITIVE : International Journal of Economic, 2022)
This study aims to analyze differences in financial performance before and during the covid-19 pandemic in manufacturing companies listed on the Indonesia Stock Exchange in 2019 - 2020 from liquidity, leverage and profitability. The research sample was 138 companies which were selected based on the purposive sampling method. The paired sample t test method was used for data analysis. The results showed that there was no significant difference in the financial performance of manufacturing companies in terms of liquidity and leverage before and during the covid 19 pandemic. In terms of profitability, there was a significant difference, namely the average decrease in profitability. Keywords: liquidity, leverage, profitability, manufacture